Pengembangan Aplikasi Mobile Augmented Reality Sebagai Media Belajar Pengenalan Dasar Huruf Hijaiyah - Adji Reno Muhammad; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The introduction and mastery of hijaiyah letters from an early age is very important, because the hijaiyah is the basis for reading and studying the holy book Al-Qur'an. But in the pronunciation, many people are still wrong in saying some hijaiyah letters that are probably caused by their mother language and habitual factors. Generally, hijaiyah letters are introduced to children as they enter kindergarten or primary school. In the learning process, sometimes there are children who have a shy nature caused by lack of bravery of children when talking to teachers or other adults, not being able to look into other people's eyes when talking, the child does not talk much, or the child is less open. Plus there are some children who tend to learn to use visual, while others tend to use audio or kinesthetic. Because of these different learning styles, it is important for teachers to use a combination of teaching methods and make the learning environment interactive and stimulating to achieve good learning outcomes. From these problems, Android-based augmented reality mobile application developed as a learning media introduction of basic hijaiyah letters. This application is developed by waterfall method. The test is validation testing, optimum condition of marker based on size and distance, and application testing. Validation testing gives results that the system is valid. Testing the optimal marker conditions gives the results that the optimal condition of the marker size 2,5x2,5cm is 4-8cm, the size of 5x5cm is 8-17cm, the size of 7,5x7,5cm is 12-26cm, the size of 10x10 is 16-34cm, and the size is 12,5x12,5cm is 19-42cm. Application testing gives results that by using the application can improve student scores by 11.19%.